Warrior trading : - Bennett, Clifford (John Wiley & Sons, 2006)
In Warrior Trading, Clifford Bennett, one of today's leading currency forecasters, outlines a path to trading success by highlighting the characteristics, the knowledge and skills, and the psychological state of mind required to be a true warrior trader. You'll be introduced to some fresh and unique perspectives regarding the markets, by looking at fundamental and technical analysis, as well as discovering how best to trade within the markets as an individual. Most importantly, you'll learn how to take advantage of those moments when the perceptions of most traders (the herd) are at odds with the underlying reality-moments when fear, greed, and other emotions wreak havoc on the ordinary trader's ability to operate objectively. Divided into three comprehensive parts, Warrior Trading will show you how to develop the focus, attitude, and mental discipline of a top trader so that you can make the most out of your time in the markets